Perancangan Sistem IoT Untuk Smart Farming Pada Tanaman Cabai Dengan Sistem Integrasi Website - Rafa Nabil Eivandra; Abd. Hallim; Arbansyah Arbansyah (Pusat Riset dan Inovasi Nasional, 2025)
The practice of chili farming in Indonesia is confronted with a number of challenges, including extreme climate conditions and limitations in irrigation management and harvest timing. The objective of this research is to design an Internet of Things (IoT) system capable of automatically and in real-time monitoring and controlling the environmental conditions of chili plants. The issues identified pertain to the suboptimal design of the manual irrigation system and the ad hoc assessment of fruit maturity. The practice of chili farming in Indonesia is confronted with a number of challenges, including extreme climate conditions and limitations in irrigation management and harvest timing. The objective of this research is to design an Internet of Things (IoT) system capable of automatically and in real-time monitoring and controlling the environmental conditions of chili plants. The issues identified pertain to the suboptimal design of the manual irrigation system and the ad hoc assessment of fruit maturity.